Large-area and efficient perovskite light-emitting diodes via low-temperature blade-coating - Shenglong Chu (Nature Portfolio, 2021)
Fabrication of efficient large-area perovskite light emitting diodes catering towards mass-production is hampered by the difficulty in getting homogenous uniform films and the high cost. Here, the authors demonstrate sol-gel engineering of low-temperature blade-coated perovskite films which can overcome these limitations.